Praktik Pencampuran Ketan Di Pajak Batu - Lubis Adek Irma Suryani; Nasution Muhammad Arsad (Jurnal El-Thawalib, 2021)
According to muamalah fiqh, buying and selling is a sale and purchase contract for certain goods where the seller clearly states the goods being traded, including the purchase price of the goods to the buyer, then he requires a certain amount of profit. Glutinous rice is a type of rice that is whiter in color than other rice. glutinous rice has a larger size when cooked, glutinous rice has a sticky texture. The problems contained in this thesis are How is the practice of buying and selling glutinous rice with a mixed system in the Batu Tax market, North Padangsidimpuan District? Why does the seller use the mixed glutinous rice system in the Batu Tax market? What is the view of muamalah fiqh on the practice of selling glutinous rice with a mixed system in the Batu Tax market? This study uses a descriptive qualitative approach in data collection, namely observation and interviews. Based on the results of the study, it can be concluded that the fiqh muamalah review of the practice of buying and selling glutinous rice in the Batu Tax Market, Padangsidimpuan District, the glutinous rice sellers commit fraud by mixing glutinous rice with ordinary rice so that the traders get greater profits. In muamalah fiqh, the practice of buying and selling mixed glutinous rice is prohibited because it contains fraud that can harm one party. Fraud in the form of quality gharar in the sale and purchase of mixed glutinous rice is one that causes harm to other people or society in general.